PENGEMBANGAN MEDIA MADING INTERAKTIF PADA PEMBELAJARAN IPAS MATERI TRADISI KELUARGA DAN MASYARAKAT PADA KELAS III SD - Fadilah, Qudrotul; Marini, Arita; Hadi, Waluyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted because science and social studies (IPAS) learning in Grade III still relied on simple learning media, creating a need for more engaging instructional materials. The study aimed to develop an interactive bulletin board learning media for the topic "Family and Community Traditions" for third-grade elementary school students. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the analysis, design, development, implementation, and evaluation stages. Data were collected through observations, interviews, expert validations, and field trials involving students using 1–4 and 1–3 Likert scales. The data were analyzed using feasibility percentages. The results showed that the interactive bulletin board media achieved feasibility scores of 85% from material experts, 89% from language experts, and 82% from media experts, all categorized as highly feasible. The limited field trial obtained a student response rate of 91%, while the wider field trial obtained 89.3%, both categorized as highly feasible. The evaluation results indicated that the developed media was appropriate for classroom use and was able to create a more engaging learning experience for third-grade elementary school students.